Analysis of Determinant Factors in Fulfilling Psychosocial and Spiritual Needs by Families in Breast Cancer Patients - Ayesie Natasa Zulka; Nugrahani, Ely Rahmatika; Mulyaning Yekti, Pinta; Vahlefi, Moch. Rizal (Jurnal Kesehatan dr. Soebandi, 2025)
Breast cancer poses not only physical but also complex psychosocial and spiritual challenges. The fulfillment of psychosocial and spiritual needs largely depends on family involvement as the primary caregivers. This study aimed to analyze the determinant factors affecting the family's ability to meet these needs. A descriptive-analytic design with a cross-sectional approach was used, involving 120 family caregivers at RS Tk. III Baladhika Husada Jember. Data were collected using a Likert-scale questionnaire and analyzed using ordinal regression. The results showed that most families provided psychosocial and spiritual support at a moderate level (80.8%). The Pseudo R-Square analysis produced a Nagelkerke value of 1.000, indicating that all independent variables fully explained the variation in the dependent variable. Although no single factor was found to be dominant, all variables had a significant simultaneous influence. These findings highlight the need for holistic and family-based interventions to enhance psychosocial and spiritual support for breast cancer patients.